Kitab “Al – ‘Arabiyah Lil Hayah” Limaharatul Kitabah ‘Ala Nadzariyati Abdurrahman bin Ibrahim Al - Fauzan - Amal, Ikhlasul (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Abstract : Writing skills in arabic teaching materials books are an important aspect that must be present. Arabiyah lil hayah TextBook became the handbook of first-year for student State Islamic University Maulana Malik Ibrahim Malang in the process of learning Arabic. All first-year students learn arabic writing skills using the book. This research was conducted to analyze the contents of Arabiyah lil Hayah (ALH) Textbook based on Describing the content of material writing skills of ALH Textbook and Describing the evaluation of writing skills in ALH Textbook according to the perspective of Abdurrahman bin Ibrahim Al-Fauzan's . This research uses a qualitative approach in the form of Library Research. The data collection in this study uses the research of documentation of the contents of the book and sorting the material and evaluation of writing skills in it to be analyzed based on al-Fauzan analysis instruments. To present data and analysis researchers using content analysis techniques. The results of the study explained that the writing skills in the Arabiyah lil Hayah Textbook is contained in each chapter with varying amounts, creative, and innovative. The form of evaluation of writing skills in the Arabiyah lil Hayah Textbook Volume 2 is in accordance to the Perspective of Abdurrahman bin Ibrahim al-Fauzan. The form of evaluation presented can help students to improve their writing skills fundamentally, creatively and innovatively.